Investigation of suspended nanoliquid flow of Eyring–Powell fluid with gyrotactic microorganisms and density number. (September 2020) - Haq, Fazal; Khan, Muhammad Ijaz; Khan, Sohail A; Hayat, T
The aim of the current investigation is to discuss the behavior of mixed convection magnetohydrodynamic flow of Eyring–Powell nanoliquid subjected to gyrotactic microorganisms over a stretchable cylinder. Energy communication is developed through the first law of thermodynamics and deliberated in the manifestation of viscous dissipation. Furthermore, Brownian motion and thermophoresis effects are also considered. Nonlinear system of partial differential equations is altered into ordinary one due to employing transformations. The given systems are then solved through ND-solve technique. Impact of influential variables on velocity, motile microorganism's temperature, and concentration is deliberated graphically. Skin friction coefficient, mass transfer rate, density number, and Nusselt number are numerically computed versus different influential variables. Velocity and temperature have opposite impact for curvature parameter. For higher estimation of fluid parameter, temperature and velocity fields boost up.